EVALUATION OF ANTIBACTERIAL ACTIVITY AND PHYTOCHEMICAL ANALYSIS OF MEDICINAL PLANT SOLANUM TRILOBATUM. - PRIYA G; CHELLARAM C (International Journal of Pharma and Bio Sciences, 2014)
The ethanolic leaf extracts of Solanum trilobatum plant were used for antibacterial study by disc diffusion method. Different concentrations (10mg/ml, 20mg/ml, 30mg/ml) of the concentrated ethanolic leaf extract were tested for its antibacterial activity against bacterial strains such Bacillusubstilis, Staphylococcus aureus, Bacillus cereus, E. Cali & Pseudomonas aeruginosa. The bacterial cultures were grown in Muller hinton agar and Muller hinton broth. The zone of inhibition was comparatively more in the concentration of 30mg/ml. Phytochemical screening of the ethanolic leaf extract of the plant revealed the presence of tannins, saponins, flavonoids, carbohydrates and alkaloids. Thin Layer Chromatography (TLC) value of the leaf extract showed the highest Retention Factor (RF) value. The plant extracts showed better inhibitory activity against the tested organisms.